Comparative metabolic profiling, enzyme inhibitory activities, and in-silico analysis of the hexane extract and the hydrodistilled oil of Boswellia serrata - Heba A. S. El-Nashar; Esraa A. Elhawary; Nilofar Nilofar; Mahmoud A. El Hassab; Taghreed A. Majrashi; Wagdy Eldehna; Gokhan Zengin; Omayma A. Eldahshan (PLoS ONE, 2026)
Frankincense ( Boswellia spp.) oleogum resin is a valuable natural source of bioactive phytoconstituents with diverse therapeutic potential. In this study, the hydrodistilled essential oil (EO) and n -hexane extract (HE) of Boswellia serrata gums were analyzed through gas chromatography–mass spectrometry (GC-MS) to determine their phytochemical composition. The GC-MS results in the identification of 62 and 71 components in the EO and HE, respectively. Acetic acid octyl ester (41.09%) and nerolidol (13.64%), were the major components of the EO. Meanwhile, incensole (28.56%), (1S,2E,4S,5R,7E,11E)-cembra-2,7,11-trien-4,5-diol (13.54%), and 24-norursa-3,12-diene (9.25%) in the HE. Regarding the antioxidant effects, the EO exhibited significantly higher antioxidant capacity compared to the HE (DPPH: 9.24 and 6.50 mg TE/g; ABTS: 25.71 and 4.94 mg TE/g), respectively. Moreover, the EO was more potent in the CUPRAC test (61.12 mg TE/g for the essential oil and 50.62 mg TE/g for HE), while the n -hexane extract (72.68 mg TE/g) showed stronger ability than the EO (13.22 mg TE/g) in the FRAP assay. The EO had a higher ability in phosphomolybdenum and metal chelation tests in comparison with the HE extracts. Further, the oil showed more potent inhibitory activity against cholinesterase, α -glucosidase, and tyrosinase than the HE extract. The HE extract was only more active on α -amylase compared to the oil. These findings suggest that olibanum EO possesses potent bioactive compounds that may contribute to the management of oxidative stress and age-related conditions, including Alzheimer’s disease, diabetes mellitus, and skin hyperpigmentation.